Influence of chloride ions concentration on the development of severe localised corrosion and its effects on the electrochemical response of the 2198-T8 alloy. (19th May 2021) - de Souza Carvalho Machado, Caruline; da Silva, Rejane Maria Pereira; de Sousa Araujo, João Victor; Xavier Milagre, Mariana; Donatus, Uyime; de Viveiros, Bárbara Victoria Gonçalves; Emil Klumpp, Rafael; Costa, Isolda
ABSTRACT: The development of severe localised corrosion (SLC) on the 2198-T8 alloy was investigated in solutions of various NaCl concentrations (0.001, 0.005 and 0.01 mol L −1 ). Immersion tests, optical profilometry, conventional and local electrochemical analyses were performed to evaluate the corrosion behaviour of the alloy. Immersion tests showed that the alloy is susceptible to SLC in all conditions, although the pits sizes were dependent on the solution concentration. The largest anodic areas, corresponding to SLC sites, were observed for the sample immersed in 0.001 mol L −1 NaCl, whereas pits with similar sizes were observed for the samples immersed in solutions with 0.005 and 0.01 mol L −1 of NaCl. Moreover, the maximum depth of attack was observed for the sample immersed in 0.001 mol L −1 NaCl. These results were in agreement with the scanning ion-selective electrode technique (SIET) maps which showed stronger acidification on the sample exposed to 0.001 mol L −1 NaCl solution.